ANALISIS KEBUTUHAN HARD SKILL DAN SOFT SKILL GURU SD DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Fadli Arif; Monita Utami; Yulia; Yuliane; Adriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research analyzes the hard and soft skill needs of elementary school teachers in implementing the Merdeka Belajar Curriculum in Indonesia. Through a literature study, the research identifies three main indicators: understanding of curriculum concepts and objectives, instructional design and implementation skills, and learning evaluation and reflection abilities. The findings indicate that elementary school teachers require competency enhancement encompassing in-depth knowledge of the curriculum, ability to design student-centered learning, and holistic evaluation skills. Necessary hard skills include mastery of curriculum structure, innovative teaching methods, and modern assessment techniques. Meanwhile, crucial soft skills include openness to change, creativity, and self-reflection abilities. The study concludes that comprehensive and continuous professional development for teachers is essential to effectively support the implementation of the Merdeka Belajar Curriculum. Recommendations include integrated training programs, establishment of professional learning communities, and creation of a supportive educational ecosystem. The implementation of this curriculum is viewed as a dynamic process requiring ongoing evaluation and adjustment to improve the quality of elementary education in Indonesia.